Method for improving coercive force of neodymium-iron-boron magnet

Through vacuum heat treatment and optimization processes, the distribution of rare earth-rich phases in neodymium iron boron magnets is improved, and the problem of insufficient coercive force in the existing technology is solved, coercive force improvement and production simplification are achieved, and it is suitable for industrial applications.

CN119132771APending Publication Date: 2024-12-13ZHEJIANG DONGYANG DMEGC RARE EARTH MAGNET CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410850303.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the coercive force of neodymium iron boron magnets, especially due to the insufficient distribution uniformity of rare earth-rich phases, which limits the improvement of the performance of the magnets, and commonly used methods increase production complexity and cost.

Method used

By vacuum heat treatment of the flip, the temperature is controlled at 450~600℃, the powder is prepared by combining hydrogen breaking and airflow grinding, and cold isostatic pressure and vacuum sintering are carried out to optimize the distribution of rare earth-rich phases and reduce the block-shaped rare earth-rich phases. Improve the coercive force of the magnet.

Benefits of technology

It significantly improves the coercive force of neodymium iron boron magnets, simplifies the process flow, reduces costs, and maintains the stability of other magnetic properties, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119132771A_ABST
    Figure CN119132771A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving coercive force of a neodymium-iron-boron magnet. The method comprises the following steps: taking raw materials of each element of the neodymium-iron-boron magnet according to a component proportion, and smelting and casting to obtain a throwing sheet; performing vacuum heat treatment on the throwing sheet at the temperature of 450-600 DEG C, performing hydrogen demolishing and airflow grinding on the throwing sheet subjected to vacuum heat treatment to obtain powder, performing orientation molding on the powder to obtain a green body, performing cold isostatic pressing on the green body, and finally performing vacuum sintering to obtain the neodymium-iron-boron magnet. Heat treatment below the ternary eutectic temperature is carried out on the throwing piece, distribution of a rare earth-rich phase in the throwing piece is improved through solid-phase diffusion, the rare earth-rich phase extends to the periphery of a columnar crystal, blocky rare earth-rich phases are reduced, rare earth loss in the jet milling stage is reduced, components are closer to nominal components, and the rare earth loss is reduced. And the proportion of rare earth-rich phases attached to the surfaces of airflow fine powder particles is increased, so that the coercive force of the sintered magnet is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth permanent magnet materials, and in particular relates to a method for improving the coercive force of a neodymium iron boron magnet. Background Art

[0002] Rare earth neodymium iron boron magnetic materials are widely used in wind power generation, new energy vehicles, consumer electronics and other fields due to their excellent magnetic energy product, playing an important role in economic and social development.

[0003] In industrial production, the residual magnetization intensity of sintered NdFeB can reach up to about 15kGs, which can reach about 95% of its theoretical value (Ms=16kGs). However, without adding heavy rare earth, the coercivity of NdFeB can only reach about 13-14kOe, which can only reach its theoretical value (H A =7.6T) by about 20%. This is partly due to the defects in the grain boundaries. The discontinuity of the grain boundaries reduces the degree of decoupling between grains and reduces the resistance to domain wall displacement.

[0004] Improving grain boundary continuity and reducing defects to increase the degree of decoupling between grains are effective methods to improve coercivity. The methods used in the prior art mainly include the following: 1. Adding low melting point metals such as Al, Cu, and Ga to wet the grain boundary surface. 2. Performing heat treatment below the magnet ternary eutectic temperature to allow the rare earth-rich phase to grow on the surface of the original main phase grains through solid-state diffusion. 3. Mixing the main alloy and the auxiliary alloy in the hydrogen crushing or air flow milling stage, and mixing the powder for a long time, so that the surface of the main alloy is evenly distributed with a rare earth-rich phase.

[0005] However, the above method has the following problems: Adding too much low-melting-point metal will reduce the remanence, which is not conducive to the preparation of high remanence products.

[0006] The first and second tempering of the blank is a conventional method to improve the coercivity of NdFeB by optimizing the distribution of rare earth-rich phases, and is a common method for improving the coercivity of various NdFeB magnets. However, the coercivity that can be improved by this method is limited.

[0007] The main alloy + auxiliary alloy (dual alloy process) requires additional preparation of auxiliary alloys, the powder mixing increases the risk of oxidation, and it takes a long time to mix the powder, which increases the complexity of the production process and increases the work-in-progress inventory.

[0008] The uniform distribution of the rare earth-rich phase can improve the continuity of the grain boundaries and thus improve the coercivity. Therefore, it is necessary to develop a process method to improve the uniformity of the distribution of the rare earth-rich phase.

[0009] CN 108122652 A discloses placing a NdFeB phase-swing sheet in a vacuum sintering furnace, adjusting the pressure to less than 0.3Pa, the temperature to 920-1000°C, and maintaining for 180-300 minutes to obtain an annealed NdFeB phase-swing sheet; the annealing treatment eliminates a large amount of α-Fe phase in the NdFeB phase-swing sheet, and improves the performance of the sintered NdFeB magnet. The purpose of annealing the sheet at about 1000°C is to eliminate α-Fe, but it cannot solve the problem of improving the uniformity of the rare earth-rich phase distribution. Because the rare earth-rich phase has too good fluidity when tempered at about 1000 degrees, the rare earth-rich phase will agglomerate if treated for a long time, and the uniformity of the rare earth-rich phase cannot be improved. Summary of the invention

[0010] The purpose of the present invention is to improve the coercivity of sintered NdFeB magnets by improving the process. The present invention heat treats the sintered sheets to improve the distribution of rare earth-rich phases in the sintered sheets, reduce the blocky rare earth-rich phases, and improve the coercivity of the sintered magnets.

[0011] The technical solution adopted by the present invention is: A method for improving the coercive force of a neodymium iron boron magnet, the method comprising: The raw materials of each element of the NdFeB magnet are taken according to the composition ratio, and the sheets are obtained after melting and casting; the sheets are subjected to vacuum heat treatment at a temperature of 450-600°C, the sheets after vacuum heat treatment are subjected to hydrogen cracking and air flow grinding to obtain powder, the powder is oriented and formed to obtain a green body, the green body is subjected to cold isostatic pressing, and finally vacuum sintering to obtain the NdFeB magnet.

[0012] Furthermore, the vacuum heat treatment is performed at an absolute pressure of 0.01-0.1 Pa.

[0013] The temperature of the vacuum heat treatment is preferably 500-550°C.

[0014] The vacuum heat treatment time is preferably 4 h to 8 h.

[0015] Preferably, in the air flow milling process, the bottom spray pressure is 0.2-0.24 MPa and the grinding pressure is 0.5-0.56 MPa.

[0016] Furthermore, the grinding pressure is preferably 0.54-0.56 MPa.

[0017] Preferably, the flap is wrapped and sealed with a high temperature resistant material before the vacuum heat treatment. The high temperature resistant material may be aluminum foil, which can withstand a high temperature of 600°C without melting. The flap may also be placed in an iron box and sealed before the vacuum heat treatment.

[0018] In the technical solution of the present invention, there is no restriction on the composition of the NdFeB magnet. As long as the magnet contains a main phase and a grain boundary phase, the method of the present invention can be used to improve the coercive force of the magnet.

[0019] In the method of the present invention, the hydrogen rupture may be carried out by using conventional hydrogen rupture technology. Generally speaking, the dehydrogenation temperature of the hydrogen rupture is 540-560° C., and the dehydrogenation time is 4-6 hours.

[0020] In the method of the present invention, orientation molding is performed to obtain a green body, the green body is subjected to cold isostatic pressing, and finally vacuum sintering. These processes can all be carried out using conventional techniques in the art.

[0021] The beneficial effects of the present invention are: The present invention provides a method for improving the coercive force of a magnet by vacuum heat treatment of a sheet. In the smelting stage, the present invention performs heat treatment (450-600°C) on the sheet below the ternary eutectic temperature, and near the low eutectic transformation temperature of neodymium iron boron, the rare earth-rich phase is extended to the periphery of the columnar crystal and the blocky rare earth-rich phase is reduced by solid phase diffusion. After the sheet vacuum heat treatment, the rare earth-rich phase occupies a larger proportion on the surface of the columnar crystal and is more tightly combined. More rare earth-rich phases will be wrapped on the surface of the fine powder particles obtained after powder making. In addition, the bottom spray pressure and grinding pressure are appropriately lowered in the air flow milling stage to reduce the impact force between the powders, minimize the separation of the rare earth-rich phase and the main phase particles, reduce the bottom spray pressure and grinding pressure, and correspondingly extend the time to make the powder grinding more sufficient. In the sintering and tempering stage, the fine powder with this structure has a shorter atomic migration process in the rearrangement process of the rare earth-rich phase, which is conducive to improving the magnetic isolation effect and thus improving the coercive force.

[0022] The present invention improves the rare earth-rich phase distribution of the sintered sheet, reduces the blocky rare earth-rich phase, reduces the rare earth loss in the air flow milling stage, makes the composition closer to the nominal composition, increases the proportion of the rare earth-rich phase attached to the surface of the air flow milled fine powder particles, and increases the coercive force of the sintered magnet only by improving the sintering process without the need to add additional heavy rare earth for grain boundary diffusion. The process is simple, cost-saving, and particularly suitable for industrial production applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a cross-sectional SEM image of the sheet of Example 1 before vacuum heat treatment.

[0024] Figure 2 This is a cross-sectional SEM image of the sheet of Example 1 after vacuum heat treatment. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below with reference to specific embodiments, but the protection scope of the present invention is not limited thereto.

[0026] The raw materials of each element of the NdFeB magnet are taken according to the composition ratio, and the sheets are obtained after melting and casting; the sheets are wrapped with aluminum foil and then subjected to vacuum heat treatment at a temperature of 450-600°C for 4-8 hours, the sheets after vacuum heat treatment are subjected to hydrogen cracking and air flow grinding to obtain powder, the powder is oriented and formed to obtain a green body, the green body is subjected to cold isostatic pressing, and finally vacuum sintering to obtain the NdFeB magnet.

[0027] The hydrogen rupture may be carried out by conventional hydrogen rupture technology. Generally speaking, the dehydrogenation temperature of the hydrogen rupture is 540-560° C., and the dehydrogenation time is 4-6 hours.

[0028] In the air flow milling process, the method of the present invention lowers the bottom spray pressure and the grinding pressure, preferably the bottom spray pressure is 0.2-0.24 MPa, and the grinding pressure is 0.5-0.56 MPa.

[0029] In the method of the present invention, orientation molding is performed to obtain a green body, the green body is subjected to cold isostatic pressing, and finally vacuum sintering. These processes can all be carried out using conventional techniques in the art.

[0030] In a preferred embodiment, the pressing pressure of the orientation molding is 9-11 MPa, the oxygen content is less than 200 ppm; and the orientation magnetic field is 1.5-2.0 T.

[0031] The holding pressure of cold isostatic pressing is 200-220MPa.

[0032] The sintering temperature of the vacuum sintering is 1040-1090° C., and the heat preservation time is 8-15 hours.

[0033] During sintering, the vacuum degree is 0.001-0.01Pa, and argon gas is filled for protection. The furnace is taken out of the furnace when the furnace temperature drops below 60℃.

[0034] After vacuum sintering, aging treatment is generally performed, which includes primary aging treatment and secondary aging treatment. The temperature of the primary aging treatment is 860~920℃, and the insulation time is 3~6h. The temperature of the secondary aging treatment is 460~600℃, and the insulation time is 3~6h.

[0035] These are all conventional techniques in the art and can be adjusted according to the specific magnet composition. These process adjustments do not constitute a limitation on the technical solution of the present invention.

[0036] Embodiment 1: 1. According to the nominal composition of the main phase alloy (Pr 10 Nd 90 ) 28.4 Dy 1.5 Fe bal Co 0.5 Ga 0.3 Cu 0.2 Ti0.2 B 0.96 (wt.%) A 100 kg sheet was prepared, wrapped with aluminum foil and heat treated at 500°C with an absolute pressure of 0.01-0.1 Pa for 6 hours.

[0037] 2. The heat-treated flakes were hydrogen-decomposed to prepare coarse powder, with a hydrogen absorption time of 45 min, a dehydrogenation temperature of 550°C, and a dehydrogenation time of 330 min. 0.12 wt.% of Dongyang antioxidant was added to the obtained coarse powder and mixed for 2 hours.

[0038] 3. The bottom spray pressure and grinding pressure of the coarse powder jet mill were set to 0.24MPa and 0.56MPa respectively. The speed of the classifying wheel was 2900rpm, and the weight of the grinding chamber was 60kg. The obtained fine powder was added with 0.15wt.% of Tianjin lubricant and mixed for 3 hours. The addition of the oxidant in step 2 and the addition of the lubricant in step 3 are both conventional techniques in the art.

[0039] 4. Orientation molding is performed under an inert gas protective atmosphere to obtain a green body, which is then vacuum packaged for cold isostatic pressing. The orientation center magnetic field is 1.7T and the isostatic pressing pressure is 220MPa.

[0040] 5. Sintering process 1085℃*4h+1090*4h, then aging treatment 900℃*4h+500℃*4h, to prepare block NdFeB magnet A (sintering is carried out in a vacuum environment, the absolute pressure is 0.001-0.01Pa). The prepared magnet A is tested for magnetic properties, and the results are as shown in Table 1: Table 1 Br(kG) Hci(kOe) (BH)max(MGOe) Hk / Hci 14.18 16.2 48.81 0.97 The cross-sectional SEM image of the sheet before vacuum heat treatment is shown in Figure 1 The SEM image of the section of the sheet after vacuum heat treatment is shown in Figure 2 shown. Figure 1 It is shown in Figure 2 that before heat treatment, the white rare earth-rich phase is more aggregated. After heat treatment at 500℃ for 6 hours, Figure 2 It can be clearly seen that the white rare earth-rich phase is relatively dispersed and evenly distributed, and the agglomeration is relatively Figure 1 Greatly improved.

[0041] Comparative Example 1: 1. According to the nominal composition of the main phase alloy (Pr 10 Nd 90 ) 28.4 Dy 1.5 Fe bal Co 0.5 Ga 0.3 Cu 0.2 Ti 0.2 B 0.96(wt.%) Prepare 100 kg of pellets.

[0042] 2. The heat-treated flakes were hydrogen-decomposed to prepare coarse powder, with a hydrogen absorption time of 45 min, a dehydrogenation temperature of 550°C, and a dehydrogenation time of 330 min. 0.12 wt.% of Dongyang antioxidant was added to the obtained coarse powder and mixed for 2 hours.

[0043] 3. The bottom spray pressure and grinding pressure of the coarse powder jet mill were set to 0.26MPa and 0.58MPa respectively. The speed of the classifying wheel was 2900rpm, and the weight of the grinding chamber was 60kg. The obtained fine powder was added with 0.15wt.% of Tianjin lubricant and mixed for 3 hours.

[0044] 4. Orientation molding is performed under an inert gas protective atmosphere to obtain a green body, which is then vacuum packaged for cold isostatic pressing. The orientation center magnetic field is 1.7T and the isostatic pressing pressure is 220MPa.

[0045] 5. The sintering process is 1085℃*4h+1090*4h+900℃*4h+500℃*4h to prepare the block NdFeB magnet B (sintering is carried out in a vacuum environment with an absolute pressure of 0.001-0.01Pa).

[0046] 6. The prepared magnet B was subjected to magnetic property testing, and the results were as shown in Table 2 below: Table 2 Br(kG) Hci(kOe) (BH)max(MGOe) Hk / Hci 14.20 15.3 48.94 0.96 Comparison of the results in Table 1 and Table 2 shows that the coercive force of the magnet of Example 1 is increased by 0.9 kOe compared with that of Comparative Example 1, which is a very significant improvement, and other magnetic properties are not significantly different from those of Comparative Example 1. It can be seen that the present invention can significantly improve the coercive force through simple process improvements.

[0047] Embodiment 2: The heat treatment temperatures in step 1 of Example 1 were changed to 400°C, 450°C, 550°C, 600°C, and 700°C, respectively. The other processes were the same as in Example 1. The magnetic properties of the magnets obtained at different heat treatment temperatures are shown in Table 3 below.

[0048] Table 3 Heat treatment temperature Br(kG) Hci(kOe) (BH)max(MGOe) Hk / Hci 400℃ 14.19 15.5 48.91 0.96 450℃ 14.18 15.8 48.85 0.97 500℃ 14.18 16.2 48.81 0.97 550℃ 14.17 16.1 48.79 0.98 600℃ 14.18 15.8 48.85 0.97 700℃ 14.19 15.4 48.87 0.97 The results in Table 3 show that when vacuum heat treatment is carried out at 450-600°C, the coercivity is significantly improved compared with Comparative Example 1, and the remanence does not decrease significantly. When the temperature continues to rise to 700°C, the coercivity decreases instead.

[0049] Therefore, the preferred vacuum heat treatment temperature is 450-600°C, more preferably 500-550°C.

[0050] Embodiment 3: The grinding pressure in step 3 of Example 1 was changed to 0.52 MPa, 0.54 MPa, 0.6 MPa, and 0.62 MPa, respectively. The other processes were the same as in Example 1. The magnetic properties of the magnets obtained at different grinding pressures are shown in Table 4 below.

[0051] Table 4: Grinding pressure (MPa) Br(kG) Hci(kOe) (BH)max(MGOe) Hk / Hci 0.52 14.15 16.6 48.56 0.96 0.54 14.16 16.4 48.68 0.97 0.6 14.19 16 48.96 0.97 0.62 14.18 15.4 48.82 0.98 The results in Table 4 show that lowering the grinding pressure will lead to a decrease in remanence, but the coercive force will be greatly improved. The ideal grinding pressure is 0.5-0.56 MPa, and more preferably 0.54-0.56 MPa.

[0052] Embodiment 4: 1. According to the nominal composition of the main phase alloy (Pr 10 Nd 90 ) 28 Ce2Co 0.5 Ga 0.3 Cu 0.2 Ti 0.1 Zr 0.1 B 0.96 Fe bal (wt.%) was used to prepare the flaked sheet. 2% of high-abundance rare earth Ce was added to the flaked sheet. The flaked sheet was wrapped with aluminum foil and then subjected to vacuum heat treatment at 500°C for 4 hours with an absolute pressure of 0.01-0.1Pa.

[0053] 2. The heat-treated flakes were hydrogen-decomposed to prepare coarse powder, with a hydrogen absorption time of 45 min, a dehydrogenation temperature of 550°C, a dehydrogenation time of 330 min, and 0.12 wt.% of Dongyang antioxidant added to the coarse powder and mixed for 2 hours.

[0054] 3. The bottom spray pressure and grinding pressure of the coarse powder jet mill were set to 0.24MPa and 0.56MPa respectively. The speed of the classifying wheel was 2900rpm, and the weight of the grinding chamber was 60kg. The fine powder was added with 0.15wt.% of Tianjin lubricant and mixed for 3 hours.

[0055] 4. Orientation molding is performed under an inert gas protective atmosphere to obtain a green body, which is then vacuum packaged for cold isostatic pressing. The orientation center magnetic field is 1.7T and the isostatic pressing pressure is 220MPa.

[0056] 5. The sintering process is 1075℃*4h+1085*4h+900℃*4h+500℃*4h to prepare the block NdFeB magnet C (sintering is carried out in a vacuum environment with an absolute pressure of 0.001-0.01Pa).

[0057] 6. The prepared magnet C was subjected to magnetic property testing, and the results were as shown in Table 5 below: Table 5 Br(kG) Hci(kOe) (BH)max(MGOe) Hk / Hci 14.1 13 48.25 0.95 Comparative Example 2: 1. According to the nominal composition of the main phase alloy (Pr 10 Nd 90 ) 28 Ce2Co 0.5 Ga 0.3 Cu 0.2 Ti 0.1 Zr 0.1 B 0.96 Fe bal (wt.%) Preparation of 100 kg flaked tablets.

[0058] 2. The heat-treated flakes were hydrogen-decomposed to prepare coarse powder, with a hydrogen absorption time of 45 min, a dehydrogenation temperature of 550°C, a dehydrogenation time of 330 min, and 0.12 wt.% of Dongyang antioxidant added to the coarse powder and mixed for 2 hours.

[0059] 3. During the coarse powder jet milling process, the bottom spray pressure and grinding pressure were set to 0.26MPa and 0.58MPa respectively, the speed of the classifying wheel was 2900rpm, and the weight of the grinding chamber was 60kg. 0.15wt.% of Tianjin lubricant was added to the fine powder and mixed for 3 hours.

[0060] 4. Orientation molding is performed under an inert gas protective atmosphere to obtain a green body, which is then vacuum packaged for cold isostatic pressing. The orientation center magnetic field is 1.7T and the isostatic pressing pressure is 220MPa.

[0061] 5. The sintering process is 1075℃*4h+1085*4h+900℃*4h+500℃*4h to prepare the block NdFeB magnet D (sintering is carried out in a vacuum environment with an absolute pressure of 0.001-0.01Pa).

[0062] 6. The prepared magnet D was subjected to magnetic property testing, and the results were shown in Table 6 below: Table 6 Br(kG) Hci(kOe) (BH)max(MGOe) Hk / Hci 14.17 12.2 48.73 0.96 Comparison of the results in Table 5 and Table 6 shows that the coercive force of the magnet of the embodiment is increased by 0.8 kOe compared with the comparative example, and the coercive force is significantly improved, and other magnetic properties are not significantly different from those of the comparative example. It can be seen that the present invention can significantly improve the coercive force through simple process improvements and is suitable for various different magnet formulations.

Claims

1. A method for improving the coercive force of NdFeB magnets, It is characterized in that The method is: The raw materials of each element of the NdFeB magnet are taken according to the composition ratio, and the sheets are obtained after melting and casting; the sheets are subjected to vacuum heat treatment at a temperature of 450-600°C, the sheets after vacuum heat treatment are subjected to hydrogen cracking and air flow grinding to obtain powder, the powder is oriented and formed to obtain a green body, the green body is subjected to cold isostatic pressing, and finally vacuum sintering to obtain the NdFeB magnet.

2. The method according to claim 1, It is characterized in that The vacuum heat treatment is performed at an absolute pressure of 0.01-0.1 Pa.

3. The method according to claim 1, It is characterized in that The temperature of the vacuum heat treatment is 500-550°C.

4. The method according to claim 1, It is characterized in that The vacuum heat treatment time is 4h~8h.

5. The method according to claim 1, It is characterized in that In the air flow milling process, the bottom spray pressure is 0.2-0.24 MPa, and the grinding pressure is 0.5-0.56 MPa.

6. The method according to claim 5, It is characterized in that The grinding pressure is 0.54-0.56Mpa.

7. The method according to claim 1, It is characterized in that The flap is wrapped and sealed with a high temperature resistant material and then subjected to vacuum heat treatment.

8. The method according to claim 1, It is characterized in that The high temperature resistant material is aluminum foil.

Citation Information

Cited By

  • Sintered neodymium-iron-boron magnet and preparation method thereof

    CN120340982A